Characteristics associated with antenatally unidentified small‐for‐gestational‐age fetuses: prospective cohort study nested within DESiGN randomized controlled trial. (1st March 2023) - Relph, S.; Vieira, M. C.; Copas, A.; Alagna, A.; Page, L.; Winsloe, C.; Shennan, A.; Briley, A.; Johnson, M.; Lees, C.; Lawlor, D. A.; Sandall, J.; et al.
ABSTRACT: Objective: To identify the clinical characteristics and patterns of ultrasound use amongst pregnancies with an antenatally unidentified small‐for‐gestational‐age (SGA) fetus, compared with those in which SGA is identified, to understand how to design interventions that improve antenatal SGA identification. Methods: This was a prospective cohort study of singleton, non‐anomalous SGA (birth weight < 10 th centile) neonates born after 24 + 0 gestational weeks at 13 UK sites, recruited for the baseline period and control arm of the DESiGN trial. Pregnancy with antenatally unidentified SGA was defined if there was no scan or if the final scan showed estimated fetal weight (EFW) at the 10 th centile or above. Identified SGA was defined if EFW was below the 10 th centile at the last scan. Maternal and fetal sociodemographic and clinical characteristics were studied for associations with unidentified SGA using unadjusted and adjusted logistic regression models. Ultrasound parameters (gestational age at first growth scan, number and frequency of ultrasound scans) were described, stratified by presence of indication for serial ultrasound. Associations of unidentified SGA with absolute centile and percentage weight difference between the last scan and birth were also studied on unadjusted and adjusted logistic regression, according to time between the last scan and birth. Results: Of the 15 784 SGA babies included, SGA was not identified antenatally in 78.7% of cases. Of pregnancies with unidentified SGA, 47.1% had no recorded growth scan. Amongst 9410 pregnancies with complete data on key maternal comorbidities and antenatal complications, the risk of unidentified SGA was lower for women with any indication for serial scans (adjusted odds ratio (aOR), 0.56 (95% CI, 0.49–0.64)), for Asian compared with white women (aOR, 0.80 (95% CI, 0.69–0.93)) and for those with non‐cephalic presentation at birth (aOR, 0.58 (95% CI, 0.46–0.73)). The risk of unidentified SGA was highest among women with a body mass index (BMI) of 25.0–29.9 kg/m 2 (aOR, 1.15 (95% CI, 1.01–1.32)) and lowest in those with underweight BMI (aOR, 0.61 (95% CI, 0.48–0.76)) compared to women with BMI of 18.5–24.9 kg/m 2 . Compared to women with identified SGA, those with unidentified SGA had fetuses of higher SGA birth‐weight centile (adjusted odds for unidentified SGA increased by 1.21 (95% CI, 1.18–1.23) per one‐centile increase between the 0 th and 10 th centiles). Duration between the last scan and birth increased with advancing gestation in pregnancies with unidentified SGA. SGA babies born within a week of the last growth scan had a mean difference between EFW and birth‐weight centiles of 19.5 (SD, 13.8) centiles for the unidentified‐SGA group and 0.2 (SD, 3.3) centiles for the identified‐SGA group (adjusted mean difference between groups, 19.0 (95% CI, 17.8–20.1) centiles). Conclusions: Unidentified SGA was more common amongst women without an indication for serial ultrasound, and in those with cephalic presentation at birth, BMI of 25.0–29.9 kg/m 2 and less severe SGA. Ultrasound EFW was overestimated in women with unidentified SGA. This demonstrates the importance of improving the accuracy of SGA screening strategies in low‐risk populations and continuing performance of ultrasound scans for term pregnancies. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.